Optical fiber sensor for ultrasonic detection at high temperature - Fengming YU; Yoji OKABE (Nihon Kikai Gakkai ronbunshu, 2017)
Because of the stable material property of optical fiber up to 1000℃, fiber-optic Bragg grating (FBG) sensor is considered as one of possible ultrasonic sensors used at ultrahigh temperature. However, disappearance of reflectivity of a normal FBG in the high temperature above 900℃ makes the ultrasonic detection impossible. In order to detect ultrasonic wave under high temperature environments, we conducted an anneal heat treatment to produce a regenerated fiber Bragg grating (RFBG) sensor. Because the RFBG has a stable reflectivity even at temperature of 1000℃, we detected the ultrasonic wave successfully at the temperature. Especially, because a π-phase-shifted FBG (PSFBG) was used as the seed grating, the RFBG sensor possessed very short effective gauge length that resulted in a broad bandwidth response to ultrasonic wave over 1 MHz. Hence, we believe that the ultrasonic RFBG sensors could be potentially applied for ultrasonic detection in non-destructive tests to evaluate microscopic damage in materials under extreme high-temperature environment.